2012
DOI: 10.1152/jn.00025.2012
|View full text |Cite
|
Sign up to set email alerts
|

Increasing SK2 channel activity impairs associative learning

Abstract: McKay BM, Oh MM, Galvez R, Burgdorf J, Kroes RA, Weiss C, Adelman JP, Moskal JR, Disterhoft JF. Increasing SK2 channel activity impairs associative learning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…We previously showed that a semi-chronic treatment with CX929 reversed the behavioral deficit and re-established normal levels of freezing in response to context and cue (Baudry et al, 2012). Manipulations of SK2 activity have been shown to influence learning performance in various paradigms (Deschaux et al, 1997; McKay et al, 2012; Stackman et al, 2002). A recent study showed that apamin enhanced contextual fear memory in WT mice conditioned with one CS-US pairing protocol, but not with three CS-US pairings (Vick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that a semi-chronic treatment with CX929 reversed the behavioral deficit and re-established normal levels of freezing in response to context and cue (Baudry et al, 2012). Manipulations of SK2 activity have been shown to influence learning performance in various paradigms (Deschaux et al, 1997; McKay et al, 2012; Stackman et al, 2002). A recent study showed that apamin enhanced contextual fear memory in WT mice conditioned with one CS-US pairing protocol, but not with three CS-US pairings (Vick et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The AHP is larger in aged compared to young animals (Landfield & Pitler, 1984; Potier et al , 1992; Disterhoft et al , 1996; Hemond & Jaffe, 2005; Tombaugh et al , 2005; Kumar & Foster, 2007; Gant et al , 2011), thus reducing the amplitude or duration of this hyperpolarizing potential may help combat age-related memory dysregulation by allowing cells to participate within a functional network (Gant & Thibault, 2009). Indeed, it has been shown that elevating potassium channel activity impairs learning (McKay et al , 2012), while lowering L-VGCC contribution to the AHP reduces the AHP (Moyer et al , 1992; Gamelli et al , 2011) and enhances learning (Deyo et al , 1989; Moyer et al , 1992). Moreover, increasing cholinergic neurotransmission which enhances cellular excitability also can enhance learning (Saar et al , 1998; Oh et al , 1999; Saar et al , 2001; Disterhoft & Oh, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of SK channels blocks conditioning-induced excitability changes in both CA1 pyramidal neurons and interneurons, and impairs learning (McKay et al, 2012, 2013). Because SK channels play a critical role in regulating after hyperpolarizing (AHP) currents and thus firing rates in CA1 (Pedarzani et al, 2005), excitability changes associated with SK channel reductions may mediate the firing rate increases we see in vivo after CFC.…”
Section: Discussionmentioning
confidence: 99%